CCL2 and CCR2 Expression in Broncoalveolar Lavage Fluid of Cynomolgus Macaque Model Of Asthma - Sela S Mariya; Fitriya N Dewi; Villiandra Villiandra; Yasmina A Pramastri; Diah Iskandriati; Eric Hayes; Joko Pamungkas; R.P Agus Lelana; Ligaya I Tumbelaka; Dondin Sajuthi (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Background: Animal models are essential for the development and improvement of novel and effective methods for diagnostic and treatment of human diseases. Cynomolgus monkeys have been used as animal model in asthma studies wherein they exhibited different responses to allergen exposure in the airway; some were low responders while others were high responder. CCL2 is a potent chemotactic factor for monocytes and the gene expression was high in animal model of asthma. The aim of this study was to evaluate CCL2 and CCR2 expression between the low and high responders. Methods: Realtime PCR technique was used to evaluate CCL2 and CCR2 gene expression in bronchoalveolar lavage samples. The subject of this study was asthmatic cynomolgus monkeys, consisted of 4 low responders and 4 high responders. This study was held in Biotechnology Laboratory of Primate Research Center LPPM IPB on October 2016- January 2017. Results: CCL2 and CCR2 expression in low responders were higher than those in high responders at 24hours post airway challenge. Conclusion: CCL2 may potentially be developed as target for therapy or a genetic marker for asthma responsiveness in individuals. (J Respir Indo 2018; 38(2): 115-22)